2012
DOI: 10.1038/cdd.2012.5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of mitochondrial protein misfolding in Drosophila melanogaster

Abstract: Protein misfolding has a key role in several neurological disorders including Parkinson's disease. Although a clear mechanism for such proteinopathic diseases is well established when aggregated proteins accumulate in the cytosol, cell nucleus, endoplasmic reticulum and extracellular space, little is known about the role of protein aggregation in the mitochondria. Here we show that mutations in both human and fly PINK1 result in higher levels of misfolded components of respiratory complexes and increase in mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
124
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(129 citation statements)
references
References 30 publications
4
124
0
Order By: Relevance
“…Considering the proposed functions of i-AAA in mitochondrial proteostasis, we assessed the amount of HSP60, a marker for the unfolded protein response in mitochondria (UPR mt ). 40,41 Western blot analysis showed that HSP60 was more abundant in dYME1L del flies compared with that in wild-type flies throughout adulthood (Figure 6a), supporting the idea that mitochondrial i-AAA protease deficiency disrupts mitochondrial protein homeostasis, leading to an elevated mitochondrial unfolded protein stress.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…Considering the proposed functions of i-AAA in mitochondrial proteostasis, we assessed the amount of HSP60, a marker for the unfolded protein response in mitochondria (UPR mt ). 40,41 Western blot analysis showed that HSP60 was more abundant in dYME1L del flies compared with that in wild-type flies throughout adulthood (Figure 6a), supporting the idea that mitochondrial i-AAA protease deficiency disrupts mitochondrial protein homeostasis, leading to an elevated mitochondrial unfolded protein stress.…”
Section: Resultssupporting
confidence: 57%
“…Indeed many mitochondrial mutations perturbing mitochondrial proteostasis compromise complex I. 41,56 Flies carrying the Drosophila Sicily mutation that disrupts complex I assembly also display reduced complex I activity, elevated ROS level and retinal degeneration. 56 However, there is no detectable apoptosis in the Sicily mutant, suggesting the existence of caspase-independent cell death and the insufficiency for ROS alone to elicit apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, mitochondrial proteotoxic stress was shown to induce mitophagy in Drosophila melanogaster (29); however, the mechanism remains unknown.…”
mentioning
confidence: 99%
“…Similar to p62, Ref(2)P accumulates with ubiquitin-containing protein aggregates in the brain of autophagy-deficient and neurodegenerative mutants of Drosophila (39,44). Ref (2)P is involved in maintenance of the viable mitochondria pool by acting downstream of Pink1 and Parkin, where Ref(2)P recycles excessive unfolded proteins via autophagy (69). This indicates a role for Ref (2)P as an autophagy receptor, similar to mammalian p62.…”
Section: Discussionmentioning
confidence: 77%